Historical Experience of Establishment of the Children's Outpatient Care in the USSR (1930-1940) - Stella A. Sher (Union of pediatricians of Russia, 2020)
The article devoted to children's outpatient care in the USSR in the 1930s presents the results of a historical and medical study reflecting the establishment of the primary children's health care. The aim of the study is to show the functional activities of children's health centers and outpatient clinics that provided preventive and therapeutic care for children and adolescents (based on archival and literary sources). The research is relevant because it is necessary to study the historical experience of the organizational foundations of the Soviet system of children's health care in order to learn lessons from the past for solving some current problems in the modernization of the primary children's health care due to attempts to reduce government involvement in medical service. The analysis of the study has shown that all measures for increasing the number of outpatient clinics, improvement of the quality of therapeutic and preventive activities enabled to achieve greater coverage with medical care for children in the USSR, to promote better and timely medical care, and to reduce children morbidity and mortality.